Exploring food security/insecurity determinants within Venezuela's complex humanitarian emergency - Marianella Herrera-Cuenca; Maritza Landaeta-Jiménez; Pablo Hernandez; Yaritza Sifontes; Guillermo Ramírez; Maura Vásquez; Thais Maingon (Elsevier, 2022)
Introduction: The complex humanitarian emergency that Venezuela has been going through for several years has deteriorated the quality of life of its citizens, deepened food insecurity in households and has promoted migratory movements of almost six million people to neighboring countries. Objective: To analyze food security in Venezuelan households to identify the determinant factors that might contribute to the design of evidence-based public policies. Materials and methods: A non-probabilistic survey of national scope was used in 2,041 urban and non-urban households. A descriptive statistical test was performed to analyze demographic variables and the three component indicators of the food security index (FSI): food consumption, economic vulnerability and coping strategies. The FSI was built according to the World Food Program (WFP) methodology, and a segmentation analysis was applied using the Chi-squared Automatic Interaction Detection (CHAID) algorithm to specify the influence of some variables as the best predictor at each level. Results: Only 9% of the households presented food security, 69% classified as marginally secure, and 22% presented moderate or severe food insecurity. The food consumption score (FCS) was the variable that best discriminated the level of food security, followed by coping strategies and the percentage of spending on food. Conclusion: Most of the households studied sacrifice their livelihoods to feed themselves and cover the minimum of their nutritional requirements. This needs attention to stop and reverse the deterioration within a framework of respect for the human rights to health and food.